Feasibility Study on Gasification of Coconut Palm Fronds - Kumannan, Sukendran (2018)
Coconut tree (Cocos Nucifera) has parts that can be classified as biomass wastes e.g. coconut husks, coconut shells, coconut trunk and coconut fronds. Coconut frond is the mid rib of the coconut tree leaves. In this work, a study was carried out on the syngas quality from gasification of coconut fronds which has potential to be gasified. However, there is lack of research for the feasibility of gasification of coconut palm fronds and hence a systematic study on the gasification of coconut fronds is required. The objective of this work is to study the characteristics of coconut fronds and quality of syngas produced from downdraft gasification. In this work, a pilot scale downdraft reactor was used for the gasification experiments. The parameters involved are temperature of the reactor, air flow rate and particle size. The fronds are obtained from coconut palm and the leaflets are removed. The frond is cut into few samples to monitor the moisture content loss along the fronds. The moisture loss is determined by the difference of the initial mass and final mass after dried. By using research surface methodology (RSM) tool it is found that 15 experiments need to be carried out to obtain the composition of gas yield, heating values, carbon conversion efficiency and cold gas efficiency. The number of experiments that was carried out was determined by the range of temperature (700 °C ~ 900 °C), air flow rate (2 l/min ~ 4 l/min) and particle sizes of 1.5 mm, 5 mm and 12 mm. The results of the experiments yield higher gas compositions when the temperature of the downdraft reactor is 900°C and air flow rate is 4 l/min, however higher syngas is produced when the particle size increases. The analysis of variable (ANOVA) from a research surface methodology (RSM) software shows that the results obtained from the experiments is almost accurate when using Box-Behnken Method. When compared to biomass like rice husk, woody biomass, other coconut waste from the literature studies, it is found that coconut frond can be gasified when compared with the syngas compositions.